Exploring the relationship between social support, resilience, and subjective well-being in athletes of adapted sport - Mira, Tânia; Jacinto, Miguel; Costa, Aldo M.; Monteiro, Diogo; Diz, Susana; Matos, Rui; Antunes, Raúl (Frontiers in Psychology, 2023)
Sports participation of people with disabilities provide an improvement in their skills, especially on access to social support, which could improve resilience and well-being. This study aims to analyse the association between types of social support (parents, coach, friend, and best friend), resilience and positive and negative affect, in 105 portuguese athletes with disabilities aged between 13 and 61 years (32 ± 12.35 years). Participants answered a short sociodemographic questionnaire, the portuguese version of the Positive and Negative Affect Schedule, and the Brief Resilience Scale, and a scale for assessing social support from parents, coach, friend, and best friend. Social support provided by the best friend, coach, friends, and parents had a direct effect on resilience and positive and negative affect. Results showed a positive and significant association between resilience and positive affect (r=0.28; p=0.004) and a negative association between resilience and negative affect (r=-0.37; p≤0.001). A strong relationship was found between resilience and affect, with no relationship being verified between the sources of social support and resilience or affect, as hypothesized. For this group of athletes with disability, more than the social support they may have or may feel, resilience proved to be very important for the consequence of sports practice in terms of subjective well-being.